Delayed Cervical Carotid Revascularization After Missile Injury: A Technical Case Report. Issue 2 (9th August 2022) - Housley, Steven B.; Waqas, Muhammad; Cappuzzo, Justin M.; Metcalf-Doetsch, William N.; Spiro, Richard M.; Levy, Elad I.
Abstract : BACKGROUND AND IMPORTANCE: Penetrating missile injury to the carotid arteries may lead to catastrophic hemorrhagic and/or ischemic complications. The incidence of carotid injury in patients with penetrating cervical trauma (PCT) is 11% to 13%, with most cases involving the common carotid artery (73%), followed by the internal carotid artery (ICA) (22%) and external carotid artery (5%). Approximately 50% of PCT cases result in mortality, with specific injury to the carotid arteries carrying nearly a 100% mortality rate. Although historically limited because most patients do not survive these serious injuries, treatment has become more feasible with advancements in endovascular techniques and technologies. CLINICAL PRESENTATION: A young man presented to our trauma center after sustaining a gunshot wound to the right neck, leading to significant hemorrhage and ultimately a Biffl grade IV ICA injury. He was taken emergently to the operating room for cervical exploration and hemostasis. A computed tomography stroke study performed after initial stabilization revealed complete right ICA occlusion with increased time-to-peak in the right hemisphere. The patient was resuscitated to maintain sufficient cerebral perfusion pressure. Later, once hemodynamic stability was achieved, the patient underwent confirmatory angiography, followed by complete ICA revascularization using a balloon guide catheter to achieve flow arrest and placement of multiple carotid stents. He made a good neurological recovery. CONCLUSION: Endovascular carotid artery revascularization may be performed successfully in the subacute phase after PCT. The use of flow arrest obtained with a balloon guide catheter assists in preventing catastrophic hemorrhage in the event of rupture.